The Role of C-reactive Protein in Patient Risk Stratification and Treatment - Ramón Arroyo-Espliguero; María C Viana-Llamas; Alberto Silva-Obregón; Pablo Avanzas (European Cardiology Review)
Atherosclerosis is a chronic inflammatory disease. Several circulating inflammatory markers have been proposed for clinical use due to their ability to predict future cardiovascular events and may be useful for identifying people at high risk who might benefit from specific treatment to reduce this risk. Moreover, the identification of new therapeutic targets will allow the development of drugs that can help reduce the high residual risk of recurrence of cardiovascular events in patients with coronary artery disease. The clinical benefits of reducing recurrent major cardiovascular events recently shown by canakinumab and colchicine have renewed the cardiology community’s interest in inflammation as an aetiopathogenic mechanism for atherosclerosis. This review explores the use of C-reactive protein, which is the most frequently studied biomarker in this context; the concept of residual risk in primary and secondary cardiovascular prevention; and the current recommendations in international guidelines regarding the role of this inflammatory biomarker in cardiovascular risk stratification.